The Effects of Genetic 3-Mercaptopyruvate Sulfurtransferase Deficiency in Murine Traumatic-Hemorrhagic Shock. Issue 4 (April 2019) - Gröger, Michael; Wepler, Martin; Wachter, Ulrich; Merz, Tamara; McCook, Oscar; Kress, Sandra; Lukaschewski, Britta; Hafner, Sebastian; Huber-Lang, Markus; Calzia, Enrico; Georgieff, Michael; Nagahara, Noriyuki; et al.
ABSTRACT: Introduction: Hemorrhagic shock is a major cause of death after trauma. An additional blunt chest trauma independently contributes to mortality upon the development of an acute lung injury (ALI) by aggravating pathophysiological consequences of hemorrhagic shock. The maintenance of hydrogen sulfide availability is known to play an important role during hemorrhage and ALI. We therefore tested the impact of a genetic 3-mercaptopyruvate sulfurtransferase mutation (Δ3-MST) in a resuscitated murine model of traumatic-hemorrhagic shock. Methods: Anesthetized wild-type (WT) and Δ3-MST mice underwent hemorrhagic shock with/without blunt chest trauma. Hemorrhagic shock was implemented for 1 h followed by retransfusion of shed blood and intensive care therapy for 4 h, including lung-protective mechanical ventilation, fluid resuscitation, and noradrenaline titrated to maintain a mean arterial pressure at least 50 mmHg. Systemic hemodynamics, metabolism, and acid-base status were assessed together with lung mechanics and gas exchange. Postmortem tissue samples were analyzed for immunohistological protein expression and mitochondrial oxygen consumption. Results: 3-MST-deficient mice showed similar results in parameters of hemodynamics, gas exchange, metabolism, acid base status, and survival compared with the respective WT controls. Renal albumin extravasation was increased in Δ3-MST mice during hemorrhagic shock, together with a decrease of LEAK respiration in heart tissue. In contrast, mitochondrial oxygen consumption in the uncoupled state was increased in kidney and liver tissue of Δ3-MST mice subjected to the combined trauma. Conclusions: In summary, in a resuscitated murine model of traumatic-hemorrhagic shock, 3-MST deficiency had no physiologically relevant impact on hemodynamics and metabolism, which ultimately lead to unchanged mortality regardless of an additional blunt chest trauma.